PENGARUH PRAKERIN TERHADAP MINAT BERWIRAUSAHA SISWA DI SMK MUHAMMADIYAH 2 PALEMBANG - Lestari, Neta Dian; Hayati, Sari (Graduate Program Magister Manajemen Pendidikan, 2019)
Praktek Kerja Industri (PRAKERIN) is a skill program in the form of learning while working or working while studying in each odd semester of class XI each year. The method used in this study was quantitative. The results can be seen that with the holding of Industrial Work Practices can grow interest to open their own business (Entrepreneurship). Judging from the data analysis Question Frequency of Very High value that is 31,25%, High Frequency 53,125%, Frequency Medium 6,25%, Low Frequency 9.375%, and Very Low 0 from Frequency of Interest Questionnaire Analysis Entrepreneurship can be seen that the average interest in entrepreneurship High frequency. t arithmetic = 6.143 and t table on Î± 0.05 / 2 dk 32 - 2 = 2.04 then this proves that there is Influence of Achievement of Industrial Work Practices on Student Interest in Computer Engineering and Network 1 SMK Muhammadiyah 2 Palembang Lesson Year 2017 / 2018. It turned out that the influence of Industrial Work Practice achievement of 0.7202 = 0.5184 or 51.8% on the criteria is quite high (strong), the remaining 48.16% influenced by other factors. The results show students who have done or who have followed the Industrial Work Practice if the value of â€œGoodâ€ Manufacturing Practice then the higher interest also for Entrepreneurship after graduating from school.